Pedagogical affordances of Extended Reality for education to territory: A literature review - Damiana Luzzi; Stefano Scippo; Stefano Cuomo; Maria Ranieri (Ricerche di Pedagogia e Didattica)
The pedagogical affordances of Extended Reality (XR) are extensively documented, particularly in the fields of medicine and teacher training, yet remain underexplored in the context of education to territory. This contribution provides an overview of studies on XR technology in this field, involving keyword selection related to XR, heritage education, landscape education, and place-based education. The 23 selected articles were analyzed based on content focus (more geographic or more historical-artistic) and methodological approach. Literature confirms that XR technologies in territorial education can enhance learning outcomes, interest, and participant engagement. However, future research should prioritize empirical studies with experimental or quasi-experimental designs to provide robust evidence of XR benefits in these dimensions. Future literature reviews should explore additional disciplinary perspectives within the complex domain of territorial education.